2006
DOI: 10.1111/j.1744-7909.2006.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Soil Respiration on Soil Temperature and Soil Moisture in Successional Forests in Southern China

Abstract: The spatial and temporal variations in soil respiration and its relationship with biophysical factors in forests near the Tropic of Cancer remain highly uncertain. To contribute towards an improvement of actual estimates, soil respiration rates, soil temperature, and soil moisture were measured in three successional subtropical forests at the Dinghushan Nature Reserve (DNR) in southern China from March 2003 to February 2005. The overall objective of the present study was to analyze the temporal variations of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 42 publications
(16 reference statements)
3
36
2
2
Order By: Relevance
“…A talaj mikrobiális eredetű CO 2 kibocsátását a talaj szerves széntartalma, valamint az egyik elsődleges környezeti változó, a talaj nedvességtartalma erősen befolyásolja (DAVIDSON et al, 2000;TANG et al, 2006). A talaj nedvességtartalmát az előző fejezetben tárgyaltuk.…”
Section: Talajlégzés (Co 2 Kibocsátás)unclassified
“…A talaj mikrobiális eredetű CO 2 kibocsátását a talaj szerves széntartalma, valamint az egyik elsődleges környezeti változó, a talaj nedvességtartalma erősen befolyásolja (DAVIDSON et al, 2000;TANG et al, 2006). A talaj nedvességtartalmát az előző fejezetben tárgyaltuk.…”
Section: Talajlégzés (Co 2 Kibocsátás)unclassified
“…5). Studies reported that soil temperature among numerous environmental factors plays an important role to affect soil CO 2 emissions (Han et al 2007;Tang et al 2006b;Wood et al 2013;Zanchi et al 2014). A report found that soil CO 2 emissions significantly correlated with soil temperature (R 2 = 0.87, P < 0.01) in the pine forest ).…”
Section: Effects Of Soil Properties On Co 2 Fluxmentioning
confidence: 99%
“…This is probably because of the seasonal variation of environmental factors (Table 1). In other words, the seasonality of soil respiration coincides with the seasonal climate pattern, with high respiration rates in the hot humid season and low rates in the cool dry season (Itoh et al 2012;Tang et al 2006b). Moreover, we observed an interesting phenomenon that the CO 2 flux showed significant fluctuations during the wet season, from July 2013 to December 2013 and from May 2014 to June 2014 (P < 0.01), but only slight fluctuations during the dry season, from November 2013 to April 2014 (P > 0.05) (Fig.…”
Section: Variations Of Co 2 Fluxes Among the Three Forest Typesmentioning
confidence: 99%
“…such an approach causes a significant diversification of co 2 emission values, even if the difference of concentrations as per gauge readouts at the beginning and end of the measurement was identical for different times of day. many authors suggest that temperature as well as other atmospheric factors influence the co 2 exhalation process (davidson et al 1998, Tang et al 2006Tang et al , riederer et al 2014). Parkin and Venterea (2010) claim that temperature differences can have a marked effect on biological activity.…”
Section: Description Of Emission Calculationmentioning
confidence: 99%
“…updegraff et al (1995) suggest that the change in carbon balance may depend on trophic status and biological activity. other researchers list the following as important factors: variability of volumetric density and differences in the ability to retain carbon by the biomass composed of different species of organisms (raich and schlesinger 1992, Thomas et al 1996), or variability of atmospheric conditions -mainly air temperature and pressure (moore and dalva 1993, davidson et al 1998, Tang et al 2006Tang et al , riederer et al 2014. recent climate change predictions suggest that conditions may become drier and will affect a part of the bog carbon resource.…”
mentioning
confidence: 99%